Learning curve of single-port laparoscopic appendectomy in a low-volume hospital - Jeong, Ji Yoon; Kim, Hyoung-Il (Frontiers in Surgery, 2025)
IntroductionSingle-port laparoscopic appendectomy (SPLA) has gained popularity, particularly among young patients, due to its cosmetic advantages. However, its adoption by surgeons in resource-constrained environments remains limited. This study assessed the learning curve of SPLA performed at a low-volume hospital (LVH).MethodsThis retrospective study included patients who underwent appendectomy between May 2022 and December 2024 at a military hospital. A single surgeon newly initiated SPLA, while other surgeons performed conventional laparoscopic appendectomy (CLA). Clinical outcomes of SPLA were compared to CLA. The learning curve of SPLA was assessed using the moving average method and cumulative sum (CUSUM) analysis of the operation time.ResultsAmong 302 patients in the study, 125 underwent SPLA and 177 underwent CLA. The mean (range) age was 22.3 (18–49), similar in both groups. The mean (range) body mass index was 23.9 kg/m2 (16.9–34.9) in SPLA, 24.2 kg/m2 (17.2–36.8) in CLA. There were no significant differences in the mean operation time or postoperative surgical complication rates between SPLA and CLA (Operation time: SPLA 48.6 min vs. CLA 47.1 min, P = 0.582; Postoperative surgical complication rate: SPLA 4.8% vs. CLA 5.1%, P = 0.911). Based on a two-breakpoint regression of the CUSUM of SPLA operation time, three learning phases were divided: the initial phase (1st–13th cases), the competent phase (14th–36th cases), and the mastery phase (37th–125th cases). The mean operation time significantly decreased throughout the phases (70.6 min vs. 52.0 min vs. 44.5 min, P < 0.001). A trend toward reduced use of additional rescue analgesics and postoperative complication rates in the mastery phase was observed but did not reach statistical differences (Additional rescue analgesics: 38.5% vs. 39.1% vs. 20.2%, P = 0.068; Postoperative complication rate: 15.4% vs. 4.3% vs. 3.4%, P = 0.101).ConclusionThe learning curve for the SPLA in a low-volume hospital consisted of three phases. The competent phase was achieved after the 13th case, and the mastery after the 36th. With sufficient prior laparoscopic experience, surgeons may safely adopt SPLA in low-volume settings, particularly when initiated in young, healthy, and non-obese patients.